Characterization of PM10 concentration and identification of Polycyclic Aromatic Hydrocarbon (pah) compound from urban and rural schools in kelantan. - Hemamalini Manogaran (2017)
Urban area with extensive transportation was associated with higher concentration of air pollutant than rural site. Particulate matter, PM10 was a major pollutant of concern as it can be adsorbed with toxic substances like heavy metals and organic compounds like polycyclic aromatic hydrocarbon compounds (PAH). Sampling was done in urban and rural schools of Kelantan from April, 2016 till June, 2016. The samples were then extracted through ultrasonification process and centrifuged before being concentrated to near dryness. 900 μL of n-hexane and 100 μL of pyrene d-10 was added prior being analyzed using GC-MS. The result shows PM10 concentration in the range of three months in Kota Bharu ranged between 24.86 μg/m3 and 99.55 μg/m3 and for Jeli it ranged between 18.01 μg/m3 and 86.05 μg/m3 respectively. The mean concentration of PM10 for Kota Bahru was higher than Jeli with 52.57 μg/m3 and 39.21 μg/m3, respectively. But, result from Independent Sample t-Test shows no significant difference with p-value of 0.083. The PAH detected in both urban and rural sample, 1-methylnaphthalene was classified as Low Molecular Weight (LMW). Human activity and meteorological factors might cause fluctuation in the concentration of PM10. We can conclude that the concentration of PM10 in urban site (SMK Kubang Kerian 1) is higher than rural site (SK Batu Melintang) but p-value was not significantly different with p-value of 0.083 due to fluctuational characteristics of PM10. The 1-methylnaphthalene was PAH with low molecular weight can impose fewer risk to the school children.